Open Innovation's Knowledge-Taking Complex Is a Dilemma within the Openness Paradox (International Journal of Innovative Research in Engineering & Management, 2021)
For companies' creative talents and outcomes, effective  search and convergence of internal and external knowledge  becomes more and more crucial. In order for companies to  reach this objective, they participate in numerous open  innovation connections to create and capture value in multi stakeholder situations. Due to the contradictory position of  essential information, difficulties might give rise to a  transparency paradox. It explores the idea of a paradox in a  paradox, which is found in the paradox of openness. We  integrate a viewpoint of knowledge and develop a  mathematical model that reveals crucial ways to control these  pressures to the other direction through innovative  information uncertainty. This unsafeness exacerbates the  tensions of transference by complexing information transfer  and integration across organisational borders and alleviating  the possibility of tackling these key conflicts of information  by defining differentiating and consolidating processes to  promote simultaneous sharing of knowledge while reducing  the risk of disclosure.
Keywords: External Knowledge; Knowledge Search; Organizational Boundaries; Paradox of Openness; Value Capture; Value Creation